A comprehensive review on the advances in renewable wind power technology. Issue 2 (April 2023) - Parimala, Patri Venkata Sesha Sudha Arundathi; Sharma, Dhruv; Mathew, Ribu
In recent years, renewable energy generation, storage, and transmission has been the focus of research. Extraction of power from renewable energy sources is increasing rapidly. Progressively more wind farms are being fastened to the power grid. Large-scale merging of wind farms into electrical power grid presents a few challenges like voltage stability, system operation and control, and power quality due to usage of power electronic converters presenting a major bottleneck. This paper elucidates various types of wind power plant technologies, consequences of power electronic converters and reviews various types of system strength determination methods.